2007
DOI: 10.1038/nnano.2007.412
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-mediated magnetoelectricity in complex oxide heterostructures

Abstract: The search for a general means to control the coupling between electricity and magnetism has intrigued scientists since Ørsted's discovery of electromagnetism in the early 19 th century.While tremendous success has been achieved to date in creating both single phase and composite magnetoelectric materials, the quintessential electric-field control of magnetism remains elusive.In this work, we demonstrate a linear magnetoelectric effect which arises from a novel carriermediated mechanism, and is a universal fea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
268
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(282 citation statements)
references
References 48 publications
(60 reference statements)
14
268
0
Order By: Relevance
“…It was predicted that atomic displacements at the FM/FE interface caused by FE switching change the overlap between atomic orbitals at the interface, which in turn affects the interface magnetization 4,5 . Recently it was demonstrated that ME effect can be induced by free carriers 6 . In this case, due to spin-dependent screening 7 , an applied electric field produces an accumulation of spin-polarized electrons or holes at the metal-insulator interface resulting in a change of the interface magnetization 8 and the exchange splitting [9][10][11] .…”
mentioning
confidence: 99%
“…It was predicted that atomic displacements at the FM/FE interface caused by FE switching change the overlap between atomic orbitals at the interface, which in turn affects the interface magnetization 4,5 . Recently it was demonstrated that ME effect can be induced by free carriers 6 . In this case, due to spin-dependent screening 7 , an applied electric field produces an accumulation of spin-polarized electrons or holes at the metal-insulator interface resulting in a change of the interface magnetization 8 and the exchange splitting [9][10][11] .…”
mentioning
confidence: 99%
“…Magnetoelectric coupling can also be mediated via an interface-charge-mediated mechanism, 132 shown in Figure 8(c). The polarization of the ferroelectric material causes a build-up of bound interface charge.…”
Section: Interfacial Magnetoelectric Coupling With Electronic Effectsmentioning
confidence: 99%
“…The magnetic spin states can also be determined by the switching of the ferroelectric polarization. Rondinelli et al [40] predicted the ME effect at the ferroelectric (dielectric)/magnetic interface using the first principles density functional calculation. Across the interface of ferromagnetic SrRuO 3 (SRO) and dielectric STO, the ferromagnetism could be controlled by the accumulation or depletion of the spin-up due to the application of the electric field on the dielectric layer.…”
Section: Charge Transfermentioning
confidence: 99%